Culinary heritage in practice: Native ingredients and hotel menu innovation - Lena N. Canet (Journal of Rural Tourism, 2026)
Purpose – This study aims to investigate the diversity of native, endemic, and heirloom ingredients in Central Luzon and to evaluate their acceptance and integration into hotel restaurant menus, particularly in relation to cultural preservation and indigenous food systems.Design/Methodology/Approach – The study adopts an exploratory sequential mixed-method design, combining qualitative exploration of indigenous ingredients and culinary traditions with quantitative assessment of their acceptance in selected hotel restaurants. This approach enables a comprehensive understanding of both cultural significance and practical applicability in the hospitality sector.Findings – The findings reveal that indigenous cuisines remain underrepresented in hotel menus despite their strong presence in local traditions, festivals, and cultural practices. The inclusion of indigenous foods is shown to strengthen cultural identity, foster reconnection among indigenous communities, and promote values of reciprocity and harmony. Additionally, food is recognized not only as sustenance but also as a form of traditional medicine. The study highlights the need for greater integration of these ingredients into contemporary culinary practices.Originality/Value – This study proposes a strategic framework for incorporating native, endemic, and heirloom ingredients into hotel restaurant menus. Its value extends beyond the culinary domain by supporting cultural preservation, economic empowerment, environmental sustainability, culinary innovation, and educational development within the tourism and hospitality industry.